Characterization of ROS Metabolic Equilibrium Reclassifies Pan-Cancer Samples and Guides Pathway Targeting Therapy - Shen, Shuai; Yan, Zihao; Wu, Jianqi; Liu, Xing; Guan, Gefei; Zou, Cunyi; Guo, Qing; Zhu, Chen; Liu, Tianqi; Chen, Chen; Chen, Ling; Cheng, Peng; et al. (Frontiers in Oncology, 2020)
Background: Abnormal redox equilibrium is a major contributor leading to tumor malignancy and treatment resistance. Understanding ROS metabolism is a key to clarify the tumor redox status. However, we have limited methods to evaluate ROS in tumor tissues and little knowledge on ROS metabolism across human cancers. Methods: The Cancer Genome Atlas (TCGA) multi-omics data across 22 cancer types and the Genomics of Drug Sensitivity in Cancer (GDSC) data were analyzed in this study. Cell viability testing and xenograft model were used to validate the role of ROS modulation in regulating treatment efficacy. Results: ROS Indexes reflecting ROS metabolic balance in 5 dimensions were developed and verified. Based on the ROS Indexes, we conducted ROS metabolic landscape across 22 cancer types and found that ROS metabolism played various roles in different cancer types. Tumor samples were classified into eight ROS clusters with distinct clinical and multi-omics features which was independent of their histological origin. We established a ROS-based drug efficacy evaluation network and experimentally validated the predicated effects, suggesting that modulating ROS metabolism improves treatment sensitivity and expands drug application scopes. Conclusion: Our study proposes a new method in evaluating ROS status and offers comprehensive understanding on ROS metabolic equilibrium in human cancers, which provide practical implications for clinical management.